Watanic jurisprudence: Governing principles in legislative powers under the federal constitution - Wan Ahmad Fauzi, Wan Husain (Parliament of Malaysia, 2022)
Before 1948, all legislative powers were vested in Malay rulers in their respective states. The Malay Rulers were the makers of the Federal Constitution through a constitutional development process, even though many parties drafted it. This paper applies the legal methodology of watanic jurisprudence. The position of Malay rulers is essential because they were sovereign authorities that legitimized the Federation of Malaya Agreement, 1948, the Federation of Malaya Agreement, 1957, and the Federal Constitution of Malaya, 1957. Previous research on this subject had ignored the principle of sovereignty as stipulated in Article 181(1) when discussing the issue of legislative powers. As a result, many parties viewed parliamentary democracy as the Malaysian principle of sovereignty. Hence, this paper intends to explain the influence of Islam and Malay customs as the governing principles of legislative powers under the Federal Constitution. This paper is important because members of the legislative, executive, and judiciary take the oath under the Sixth Schedule before discharging their respective constitutional responsibilities. This paper would assist in understanding the essence of the oath under the Sixth Schedule vis-à-vis the duty to uphold the rule of law and the supremacy of our Constitution.